Äänislinna noir - miehitetty Petroskoi suomalaisessa kirjallisuudessa - Kauhanen Riku (Sotilasperinteen seura, 2022)
Äänislinna -noir – Occupied Petrozavodsk in Finnish literature
During the Continuation War (1941–1944) the Russian city of Petrozavodsk (Petroskoi) was captured and occupied by the Finnish Army and the city was renamed as Äänislinna (from Onegaburg, literally “Onegacastle”). City became an important logistical city to the Finnish Army and it also housed the largest garrison of Finnish history. City became familiar to hundreds of thousands of Finnish soldiers and women serving in the area, thanks to crowded passenger trains which transported people to home in Finland and back to front. Thousands of Russian civilians were also relocated to the city in the Concentration / Transfer Camps. Especially during the harsh winter of 1941–1942 and spring and summer of 1942 mortality rate in these camps was very high due to famine.
Capturing the city in 1st of October 1941 was a major victory for Finnish army. City became familiar to home front thanks to articles, radio broadcasts and news films. These were produced by journalists home and abroad and soldiers serving in Propaganda Companies (TK, Tiedoituskomppania). These companies had many professional authors in their personnel. Therefor it’s not surprising, that the occupied city became a scene for many books: new city intrigued the writers and run-down shacks, old wooden houses, pompous palaces and pretentious monuments of Soviet era were portrayed in books set in Petrozavodsk.
In this article I study five books situated in the city of Äänislinna. Talo Dźerśinskajan varrella (1942) by Outsider (Aarne Haapakoski), Tapahtui Petroskoissa (1942) by Heikki Rantala, Petroskoin musta hämähäkki (Published in 1961 in Peitsi-magazine, in 1991 as a book) by Outsider, Petroskoin keltainen kissa (1980) by Mauri Sariola and Äänislinna (2011) by Pekka Manninen. Two were written during the war in the year 1942 and during the beginning of Finnish occupation, two were written after the war by authors, who themselves served in the city during the war and one is written after the war by an author, who was born after the war.
Talo Dźerśinskajan varrella (A house on the Dźerśinskaja Street) and Tapahtui Petroskoissa (Happened in Petroskoi) could be described as “pulp fiction”, the first being a detective/secret agent story written by the popular writer Outsider, pen name of Aarne Haapakoski (1904–1961). Book is a part of Outsiders detective series Karma (Karma-sarja) named after the main character detective Klaus Karma. The second book is also a detective/secret agent/adventure story by Heikki Rantala (1911–1961) with several plot lines. Both books were published at the same time in 1942 and many themes and events are similar. City is made familiar to reader with Russian street names, city squares and by describing the buildings in great detail. In both books the key element is a spy or spies left in the city to sabotage Finnish forces and spy on them. A very popular theme, which is also mentioned in other literature, are ten (or less) female spies left by the Russians. Both Haapakoski and Rantala served in Propaganda Companies and had firsthand experience of the captured city and the beginning of occupation in 1941–1942. Surprisingly both writers mention the concentration camps and Rantalas hero, lieutenant Koivu even visits a house in camp area, though the visits give almost a rosy image of the conditions of two women living in the camp. The famine and suffering of civilians are not mentioned, which is not surprising considering that the books were published during the war.
Outsider “returned” to Petrozavodsk in 1961, when the story Petroskoin musta hämähäkki (Black Spider of Petrozavodsk) was published as a serial story. The themes are very similar to Outsiders previous Petrozavodsk-book, but the story is not limited to Petrozavodsk. For example the main character Järvinen visits Berlin at one time to gain information about his adversary. Some things that were definitively a secret during the war are mentioned, for example the poor morale of some Finnish units after the occupation of the city. Female spies are mentioned soon after main character arrives to Petrozavodsk. Surprisingly this book is less detailed when portraying the city and more room is given to the actual plot.
Fourth book, Petroskoin keltainen kissa (Yellow Cat of Petrozavodsk) was written by Mauri Sariola (1942–1985) as a part of his Susikoski crime-series. Superintendent Olavi Susikoski, Sariolas main character, is however involved only at the end of the book. Most of the story follows Samuli Ilvesoja  during his visit to Petrozavodsk in 1980. Ilvesoja has arrived to the city with other Finnish tourists during the golden days of “vodka tourism” with a certain goal in his mind: he is there to regain a memento, which he buried near his service place just before Finnish evacuated the city in June of 1944. However other members of the tourist group also ha histories of their own in the city, and these stories lead to the death of one traveller. Samuli Ilvesoja is clearly the alter ego of Mauri Sariola, who himself served as a radio operator in the city, just like Ilvesoja descripes his time in the city. Petroskoin keltainen kissa is also the only book which is set in the end of Finnish occupation in 1943–1944, whereas the other books are set in 1941–1942. This is probably because Sariola served in the city during years 1943–1944. The book is mostly a memento of Äänislinna, and Ilvesoja navigates his way through the city with the help of an old war time map and his memories. City of 1944, Äänislinna, and nowadays (1980 city) Petrozavodsk merge. Crime is a lesser part of the book, and it roots this part of the story in familiar “Äänislinna-genre” or “Äänislinna-noir”: according to several travelers there was a spy among Finnish ranks during the war, and like the back cover of the book mentions: “The hand of an avenger is long”.
Äänislinna, written by Pekka Manninen (1953–), was published in 2011 and gives a very brutal image of concentration camps, going to the point of sadism. The main character Emmanuel Wolff is a young Finnish officer and a Jew, who instead of going to front lines is pointed as an intendent of the camps. Unlike the other four books, Äänislinna is not intended to be a crime/detective book but it is a modern novel: it’s not even clearly a war novel, but the war is the scenery for sad and horrific events. Manninen still uses common themes: a spy network, sabotage, well detailed street names, city plazas and buildings. Manninen also uses the same time slot as Outsider and Rantala, which is winter 1941–1942. This is probably because Manninen wanted to show the horrors which the civilians faced, but time also gives a chance to portray Russian resistance in the city.
All five books have many themes in common, so there definitively is a phenomenon which could be called “Äänislinna-noir”. First, Äänislinna is time and space, a city which existed during Finnish occupation during years 1941–1944. If studied on map, characters in books mostly move in a rather small area. This area consist of only few blocks around the Government Plaza in city center. Outside this “home” is the area of restricted movement, shanties, camps and unknown people.
The nature of occupied city, which consist of soldiers and Finnish, Carelian and Russian civilians is unique and creates an atmosphere of distrust and unclear identities. Especially the presence of spies working for Soviet Union is a common factor. Many characters are also given double-identities, thanks to the history of the city as the center of “Finnish Red Carelia” in 1920–1930s, when refugees of Finnish Civil War (1918) and Finnish-Americans immigrant workers lived in Eastern Carelia in great numbers.
Four books are set in winter 1941–1942, when the Finns were still getting to know the city better and it’s plausible for the plot that the Russians still had operating agents in the city. The most common theme is not the city itself but knowing it, and in a way, “taming” it. Books written in 1942 depict Finnish detectives weeding out Russian spies and criminals, therefore establishing some order. Books written after the war, Outsiders Petroskoin musta hämähäkki and Äänislinna by Manninen also cover this, though the eventual failure and loss of the city is present: city is occupied, but not tamed. In this sense Sariolas book is a curious one: Instead of a Russian spy, who knows the city of Petrozavodsk well and is avoiding the Finnish authority the situation is reversed: a Finn, who knows the city very well, is on rather shady business and wonders if local authorities are following him or find out what he is actually doing. Also the latest book, Äänislinna, depicts Wolff as an individual who wants to know the city better and – in a way – make it his home. But at best the city becomes home turf: never home.
Tahtoa ja terästä: näkökulmia sotilasperinteeseen IV